Mediation Role of Work Flexibility on the Linking of Work Family Conflict and Job Satisfaction - Ryan Basith Fasih Khan (University of Merdeka Malang, 2022)
This study investigates the direct and indirect effect of work family conflict on job satisfaction. As a novelty of the research, the researcher added the work flexibility variable as a moderating variable. This study uses quantitative analysis using a questionnaire as a research instrument which is distributed to as many as 113 respondents online. The sampling technique is purposive sampling. Respondents in this study were banking employees who were married. After the data is collected, then quality testing is carried out using validity and reliability tests. Furthermore, hypothesis testing using SEM-PLS with the smartpls program. The results showed that work family conflict can reduce job satisfaction, work flexibility can affect job satisfaction. As well as moderating work flexibility in the relationship between work family conflict and job satisfaction. It is hoped that further researchers can add the age control variable.